Development of Virtual Reality Media with a Deep Learning Approach to Improve Early Childhood Science Literacy Skills - Siti Aisyah; Delfi Eliza; Yaswinda; Setiyo Utoyo (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop Virtual Reality (VR)-based learning media integrated with a deep learning approach to improve early childhood science literacy skills. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The study was conducted at Bunda Musnidar Kindergarten, Padang, involving children aged 5–6 years. Data were collected through observations, interviews, questionnaires, and science literacy tests, and analyzed using validity, practicality, and effectiveness tests, including N-Gain and paired sample t-test analysis. The results indicate that the developed VR media achieved a media validity score of 91.25% and material validity of 95%, both categorized as very valid. The practicality test showed a score of 94.44%, indicating that the media is highly practical for classroom use. Furthermore, the effectiveness test revealed an N-Gain score of 0.78 (high category), supported by a significant difference between pre-test and post-test results. These findings demonstrate that VR-based learning media integrated with a deep learning approach effectively enhances early childhood science literacy. The study concludes that immersive and meaningful learning experiences facilitated through VR significantly support children’s ability to observe, explore, and understand scientific concepts in real-life contexts.